Towards a theatre of the fabulous - informed by a performative queer autoethnography on the stage of an all-boys’ school - Kotze, Sophocles (University of the Witwatersrand, Johannesburg, 2024)
As a queer teacher who felt discomfort in the homogeneousness of a traditional heteronormative space of an all-boys’ school, in this research, I explore the extent to which a performative queer autoethnography can inform the creation of a Theatre of the Fabulous (an embodied queer pedagogy), what it could look like and how it could be used as a queer pedagogical tool in the classroom through which to identify heteronormative practices and, ultimately, move towards a space which is safe for queerness. My strategy was to draw on queer theory and thinking about queer pedagogical writing. I hypothesised that heteronormativity, patriarchal and colonial practices are evident in all- boys’ schools (Connell, 2000; Pollack, 2006; Sullivan, 1995) and that, as a queer teacher, my movements are made queer. I used performance as research (PaR) as a methodology, with performative writing, in this work. Deeply exploring the personal, theoretical and practitioner’s journey, and understanding the narration itself as performance as research, this research is structured through six acts and different scenes rather than the traditional chapters and sections. As a Dramatic Arts teacher, I am programmed to see “all the [world as] a stage, and all the men and women [sic] merely players”3 and my queer reality as a linear theatre text filled with plot and intrigue. This format allowed me to express myself, stylistically and typographically, through not only academic/scholarly reading and writing, but also through the inclusion of interesting quotes I came across in my journey towards a Theatre of the Fabulous, musings and asides about my
A research report submitted in fulfillment of the requirements for the Master of Arts (in the field of Drama) i, In the Faculty of Humanities, Wits School of Art, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; theatre of the fabulous; queer autoethnography; SDG-4: Quality education